Helicobacter Pylori Infection Induced Henoch Schonlein Purpura: A Case Report - Sajana Bhandari; Deeptara Pathak Thapa (Nepal Journal of Dermatology, Venereology & Leprology)
Henoch Schonlein Purpura (HSP) also known as IgA vasculitis, is an immune complex vasculitis affecting small vessels. We report a case of 53 years old female who presented with multiple reddish-brown purpuric papules over bilateral lower limb for 10 days. Her cutaneous findings were suggestive of HSP. She also had a history of recurrent dyspepsia for the past 6 months for which she had been taking antacid from a local pharmacy infrequently. To confirm her diagnosis, skin biopsy was sent for both histopathological examination and direct immunofluorescence which were suggestive of HSP. We referred her to the medicine department for her gastrointestinal complaints where upper gastrointestinal endoscopy was performed and the finding was consistent with Helicobacter pylori (H. pylori) infection. The patient was started on a treatment regimen for H. pylori eradication which resulted in a dramatic improvement in both gastrointestinal complaints as well as cutaneous lesions. There are very few cases in the literature showing an association between HSP and H. pylori infection and none from our part of the world.